2019
DOI: 10.1002/jctb.6191
|View full text |Cite
|
Sign up to set email alerts
|

Mass transfer performance and correlations for CO2 absorption into aqueous blended PG/MEA in PTFE membrane contactor

Abstract: BACKGROUND:The method for capturing carbon dioxide (CO 2 ) with amine solution in a hollow fiber membrane contactor has been identified as a potential large-scale application technology for capturing CO 2 from flue gas. The mass transfer performance of CO 2 relies in large extent on the operating conditions, the types of absorbents and the properties of membrane materials. Therefore selecting the appropriate absorbent and studying the effect of operating parameters on the mass transfer performance become of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…In the past decades, extensive lab‐scale studies have been reported on membrane absorption (MA) for CO 2 capture using various membrane materials, such as polypropylene (PP) 4 and polytetrafluoroethylene (PTFE), 5–8 and chemical solvents, such as monoethanolamine (MEA), 4 and 4‐diethylamino‐2‐butanol (DEAB) 9 . In addition, some effective approaches are used to reduce the mass transfer resistance of membrane element, such as preparing membranes with notable hydrophobicity (to prevent membrane wetting) 10 and with asymmetric structure (to increase permeability) 11 .…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, extensive lab‐scale studies have been reported on membrane absorption (MA) for CO 2 capture using various membrane materials, such as polypropylene (PP) 4 and polytetrafluoroethylene (PTFE), 5–8 and chemical solvents, such as monoethanolamine (MEA), 4 and 4‐diethylamino‐2‐butanol (DEAB) 9 . In addition, some effective approaches are used to reduce the mass transfer resistance of membrane element, such as preparing membranes with notable hydrophobicity (to prevent membrane wetting) 10 and with asymmetric structure (to increase permeability) 11 .…”
Section: Introductionmentioning
confidence: 99%